Pengembangan Media Pembelajaran Digital Berbasis Website melalui Aplikasi Canva pada Mata Pelajaran Teknologi Perkantoran Kelas X di SMKN 31 Jakarta 2026 - Aurellia Fitrista Maharani; Puji Wahono; Muhammad Ikhwan (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to develop and evaluate the feasibility of Teknoran, a website-based digital learning medium developed through the Canva application for the Office Technology subject in Grade X at SMKN 31 Jakarta. The study was motivated by learning activities that were still dominated by lecture methods and limited learning media. Teknoran was designed to facilitate learning through integrated features such as learning materials, assignments, and educational games within a single platform. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. Data were collected through observation, needs analysis questionnaires, validation sheets from material and media experts, and student response questionnaires during one-to-one and small group trials. Data were analyzed using descriptive quantitative and qualitative techniques. The results showed that the Teknoran website achieved a feasibility score of 95% from material experts and 93.33% from media experts, both categorized as “Very Feasible.” Student responses also indicated a very high level of acceptance, with an average score of 95.68%. These findings demonstrate that Teknoran is highly feasible as a digital learning medium and can support more interactive, flexible, and independent learning in Office Technology subjects at SMKN 31 Jakarta.